Pengalaman Psikologis Remaja dengan Kondisi Penyimpangan Perilaku Seksual (Gay) (Studi Fenomenologi di Kabupaten Jember) - Abdul Aziz Azari (Universitas Islam Jember, 2018)
Gay is a life style fulfill normal needed to get in love and responsibilities through sexual intimate with guys who have equal sex. A phenomenological qualitative design that focused to find a facts about the social phenomena that aims to determinate the experience of teenagers with sexual behavior's distortion condition (gay). Five participants have been with sexual behavior's distortion condition (gay) and stay in Kabupaten Jember. Data were collected through interview then made recorded used media record (laptop) then made a transcript and gave coding. The results reveal a phenomenon about history of parenting that is permissive-indulgent parenting, permissive-neglectfull parenting, authoritarian parenting and authoritative parenting. On the other side also find the psychological’s experience about interpersonal relationship that got a data is Games people play model, Interacsional model, Role model and Social exchange model. On the other hand, there is the psychological’s experience about coping mechanisms that is Confrontative coping, Seeking for social support, Escape, Self control, Possitive reapreasial and Accepting responsibility. On the other side, the psychological’s experience about public stigma that is Stereotype, Prejudice and Dicrimination. The recommended from this research is a parent can give a right history of parenting to their children. In the other hand, the gay teenagers can use right coping mechanism to solve a problem in their life and society decrease the stigma which spotlight often to gay teenagers.